Assessing the impact of sleeve gastrectomy on micronutrient levels and inflammatory markers – a case-control study - Ajeed, Abbas Mosad; Naif, Nabaa Hassan; Farag, Aliaa Hashim; Mohsein, Osama A. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Sleeve gastrectomy has become one of the most common surgical procedures in the world recently, due to its role in promoting weight loss and reducing the risk of obesity-related diseases. This study aims to determine the levels of inflammatory and nutritional factors in patients undergoing gastric sleeve surgery. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. A case-control study was conducted including 150 patients who underwent gastric sleeve surgery and 50 healthy participants as a control group. Inclusion criteria included patients aged 45–65 years with a BMI ≥35 kg/m². Levels of interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), adiponectin, interferon-gamma, IL-10, IL-1β, monocyte chemoattractant protein-1, fasting blood glucose (FBG), serum amyloid A, iron, ferritin, calcium, and vitamin D3 were measured using enzyme-linked immunosorbent assay. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. The study revealed that the control group (22.8±3.6 kg/m²) had a significantly reduced BMI compared to the patients who underwent sleeve gastrectomy (35.5±7.1 kg/m², (p<0.001). Elevated levels of C-reactive protein, IL-6, TNF-α, and FBG were seen in the postoperative group, although adiponectin levels were dramatically reduced (p<0.001). Furthermore, the postoperative patients manifested significantly reduced levels of iron, calcium, and vitamin D3, suggesting a profound insufficiency in these vital nutrients and their possible consequences on their long-term well-being. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. The study results indicate that patients who underwent gastric sleeve surgery had significantly lower levels of iron, ferritin, calcium, and vitamin D3, compared to the control group. This is due to the effect of surgery on the absorption of nutrients, which causes a deficiency in vitamins and minerals necessary for bone and body health.